PENDEKATAN MULTIPLE OVERHEAD RATES PADA JOC SYSTEM DI PT. MGT (Fokus Ekonomi, 2011)
PT MGT is a garment company that manufactures various types of outerwear men. The process ofmanufacture or finishing of products based on the production schedule (order from the marketingdepartment). Product costing applied by companies is accumulating direct materials cost (fabricsand accessories), direct labor cost, overhead cost, washing materials cost, and retro cost. Thecompany used actual costing system to measure the production cost, so that the management cannotknow production cost reporting at any time. Job-order costing systems is the answer for thecompay’s necessity to calculating the product cost. The authors will describe job-order costingsystems step by step. There is a difference between company’s calculation version with the authorsproposed. The results of calculations performed by company to AX 037 MTWQ is Rp43, 907.28while using the job-order system is Rp42, 162.35. The results of calculations performed by companyto RPBC 073 CH / K is Rp27, 553.09, while using the job-order system is Rp23, 895.49. Thedifference is due to the differences in classification and overhead cost allocation method usingmultiple rates.Keywords: product cost, job-order costing system, cost pool, overhead rates, job order sheet